State of Libya (Springer Science+Business Media Singapore 2016, 2016)
The development of higher education in the State of Libya has been disarrayed by the ongoing civil conflict and politico-security instability. Since the fall of Gaddafi, the instability and conflict has not only affected the socioeconomic development but also in terms of higher education. While prior to that, despite being one of the biggest spenders on education in the world, higher education of Libya was confronted by problems of quality and overcrowding that were unique to the Libyan context. With the instability and conflict, the situation and prospects of higher education in Libya have further deteriorated. However, the neglect on higher education of Libya cannot be underestimated as it has a crucial role to play in the future rebuilding of what may have been deemed currently as a ‘failed state’ but with vast economic potentials.